Review of Hayden White's, Λογοτεχνική θεωρία και ιστορική συγγραφή [Literary theory and historical writing] - Lianeri, Alexandra (Historein, 2017)
Hayden White. Λογοτεχνική θεωρία και ιστορική συγγραφή [Literary theory and historical writing]. Trans. Yorgos Pinakoulas. Athens: Epekeina, 2015. 320 pp.